Fadu head and neck squamous cell carcinoma induces hyperexcitability of primary sensory neurons in an in vitro coculture model. (16th May 2022) - Uhelski, Megan L.; Gorur, Aysegul; Shi, Ted; Corrales, German; Du, Kim N.; Li, Yan; Amit, Moran; Tatsui, Claudio E.; Rhines, Laurence D.; Dougherty, Patrick M.; Cata, Juan P.
Abstract : Supplemental Digital Content is Available in the Text. Squamous cell carcinoma cells promoted an inflammatory microenvironment and induced sensitization of both human and rat dorsal root ganglion neurons in patch clamp electrophysiology recordings. Abstract: Introduction: Currently, cancer pain is viewed as a process orchestrated by the release of pronociceptive molecules and the invasion of neural structures, referred to as perineural invasion (PNI). Cancer pain resulting from PNI is well-documented, but the mechanisms leading to peripheral sensitization because of tumor growth are not fully known. Methods: A retrospective study was used to examine how the use of anti-inflammatory medications affected preoperative pain in patients with oral squamous cell carcinoma cancer. We then used an in vitro coculture model in which dorsal root ganglion (DRG) neurons were incubated together with Fadu human head and neck squamous cell carcinoma cancer cells to explore how cancer cells affect the electrical membrane properties of sensory neurons. Results: We found that inflammation contributes to preoperative pain in patients with oral squamous cell carcinoma. After coculture with Fadu human head and neck squamous cell carcinoma cancer cells, we identified markers of inflammation in coculture media and found evidence of neuronal sensitization, including spontaneous activity, reduced current thresholds, depolarized resting membrane potential, and enhanced responses to current stimulation in human and rat DRG neurons. In rats, these effects were influenced by sex and age: neurons from young adult female rats were resistant to changes in neuronal activity, in contrast to neurons from older adult female rats or male rats of either age group. Conclusions: Pro-inflammatory substances released in cancer cell–DRG coculture promoted neuronal hyperexcitability and may contribute to cancer pain after PNI, and these effects may differ across age groups and sexes.